Cross-national variation in homicides: the case of Latin America - Neapolitan, Jerome L. (International criminal justice review, 1994)
This research shows that Latin American nations have a disproportionate number of the high homicide rates that occur among the nations of the world and that all Latin American nations have at least moderately high homicide rates. An investigation of the history and culture of Latin America indicates that cultural values conducive to violence have evolved out of the history of colonization and subjugation that is shared by these nations. This research examines whether the high homicide rates can be explained by structural and demographic national characteristics that have been found to explain cross-national variation in homicides in past research. Regression analysis using World Health Organization, United Nations, and INTERPOL homicide data reveals that this region exhibits a strong positive association with homicides net other relevant variables for all indicators of homicides. The strength of the association is substantially greater than for any other variable included in the analysis. Thus it is probable that there is a strong cultural component to the high homicide rates in Latin American nations. Other possibilities are briefly discussed